1980
DOI: 10.1002/hlca.19800630725
|View full text |Cite
|
Sign up to set email alerts
|

Linear‐reactor‐infrared‐matrix and microwave spectroscopy of the cis‐2‐butene gas‐phase ozonolysis

Abstract: SummaryInvestigation of the formation of complex products in the gas-phase ozonolysis of cis-2-butene by linear-reactor-infrared-matrix and linear-reactor-microwave spectroscopy is reported. The following species have been unequivocally detected: secondary 2-butene ozonide, acetic acid, peracetic acid, glycolaldehyde, dimethyl ketene, the simple and mixed anhydrides of formic and acetic acid, 2,3-epoxybutane and 2-butanone, besides polyatomic products already known. In contrast, the primary ozonide has been de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

1981
1981
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 51 publications
0
6
0
1
Order By: Relevance
“…Heicklen et al 31 and Kuhne et al 30 both have reported two infrared absorptions near 715 and 1062 cm -1 in their earlier studies. Heicklen et al tentatively assigned these two bands, along with several other bands, to the primary ozonide of cis-2-butene, cis-dimethyl-1,2,3-trioxolone.…”
Section: Discussionmentioning
confidence: 88%
“…Heicklen et al 31 and Kuhne et al 30 both have reported two infrared absorptions near 715 and 1062 cm -1 in their earlier studies. Heicklen et al tentatively assigned these two bands, along with several other bands, to the primary ozonide of cis-2-butene, cis-dimethyl-1,2,3-trioxolone.…”
Section: Discussionmentioning
confidence: 88%
“…Beyond C 2 H 4 , no clear-cut mechanistic interpretation is available for the experimental ozonolysis data, as will be shown for the case of 2-butene isomers. The ozonolysis of 2-butenes produces CH 3 CHO and CH 3 CHOO*; 20−40% of the latter is considered to stabilize the CH 3 CHOO intermediate in the gas phase under 1 atm at room temperature. In a matrix-isolation FTIR spectroscopic study of 2-C 4 H 8 ozonolysis, Horie and Moortgat 33,34 determined quantitatively the reaction products which were attributable to the decomposition of the excited CH 3 CHOO* and noted that the carbon balance obtained by summing up the identified products was ∼60%.…”
Section: Ozonolysis Of 2-butene Isomers:  Why Is the Carbon Balance S...mentioning
confidence: 99%
“…A number of other product studies using gas chromatography or other analytical techniques have been carried out (see, for example, ref 46,[58][59][60][61][62][63][64], but since these studies have not provided information as definitive as those described above and in the following sections, these are not discussed further in this article.…”
Section: B Product and Mechanistic Studiesmentioning
confidence: 99%